Mechanisms of angioregression of the corpus luteum - Monaco, Corrine F.; Davis, John S. (Frontiers in Physiology, 2023)
The corpus luteum is a transient ovarian endocrine gland that produces the progesterone necessary for the establishment and maintenance of pregnancy. The formation and function of this gland involves angiogenesis, establishing the tissue with a robust blood flow and vast microvasculature required to support production of progesterone. Every steroidogenic cell within the corpus luteum is in direct contact with a capillary, and disruption of angiogenesis impairs luteal development and function. At the end of a reproductive cycle, the corpus luteum ceases progesterone production and undergoes rapid structural regression into a nonfunctional corpus albicans in a process initiated and exacerbated by the luteolysin prostaglandin F2α (PGF2α). Structural regression is accompanied by complete regression of the luteal microvasculature in which endothelial cells die and are sloughed off into capillaries and lymphatic vessels. During luteal regression, changes in nitric oxide transiently increase blood flow, followed by a reduction in blood flow and progesterone secretion. Early luteal regression is marked by an increased production of cytokines and chemokines and influx of immune cells. Microvascular endothelial cells are sensitive to released factors during luteolysis, including thrombospondin, endothelin, and cytokines like tumor necrosis factor alpha (TNF) and transforming growth factor β 1 (TGFB1). Although PGF2α is known to be a vasoconstrictor, endothelial cells do not express receptors for PGF2α, therefore it is believed that the angioregression occurring during luteolysis is mediated by factors downstream of PGF2α signaling. Yet, the exact mechanisms responsible for angioregression in the corpus luteum remain unknown. This review describes the current knowledge on angioregression of the corpus luteum and the roles of vasoactive factors released during luteolysis on luteal vasculature and endothelial cells of the microvasculature.